Estimation of the value of an inspection and maintenance program: A Bayesian gamma process model. (December 2021) - Yuan, Xian-Xun; Higo, Eishiro; Pandey, Mahesh D.
Abstract: This paper presents a model to quantify the economic value gained by implementation of an inspection and preventive maintenance program for managing an ageing component population. The proposed approach is a refinement of the Bayesian value of information analysis through the consideration of an intricate interaction between parameter and temporal uncertainties associated with the gamma process of degradation. This paper presents an analytical formulation and computational approach to solve this complex problem in a multivariate setting. The paper shows that the economic value is significantly sensitive to the prior information and relative costs of preventive and corrective maintenance. Since the value of inspection is dominated by a reduction in the parameter uncertainty of the gamma process model, lifecycle cost optimization which ignores this aspect would lead to a sub-optimal solution of the problem. Highlights: Economic value of an inspection and replacement program for ageing components. Solution of the value of information (VOI) problem for gamma degradation process. Study of role of epistemic & temporal uncertainties in a stochastic VOI problem. Value of synergistic effect of information in a multiple component population.